Bioorthogonal Turn‐On Probe Based on Aggregation‐Induced Emission Characteristics for Cancer Cell Imaging and Ablation. Issue 22 (15th April 2016) - Yuan, Youyong; Xu, Shidang; Cheng, Xiamin; Cai, Xiaolei; Liu, Bin
Abstract: Bioorthogonal turn‐on probes have been widely utilized in visualizing various biological processes. Most of the currently available bioorthogonal turn‐on probes are blue or green emissive fluorophores with azide or tetrazine as functional groups. Herein, we present an alternative strategy of designing bioorthogonal turn‐on probes based on red‐emissive fluorogens with aggregation‐induced emission characteristics (AIEgens). The probe is water soluble and non‐fluorescent due to the dissipation of energy through free molecular motion of the AIEgen, but the fluorescence is immediately turned on upon click reaction with azide‐functionalized glycans on cancer cell surface. The fluorescence turn‐on is ascribed to the restriction of molecular motion of AIEgen, which populates the radiative decay channel. Moreover, the AIEgen can generate reactive oxygen species (ROS) upon visible light ( λ =400–700 nm) irradiation, demonstrating its dual role as an imaging and phototherapeutic agent. Abstract : Fast and specific : A bioorthogonal turn‐on probe based on a red‐emissive fluorogen with aggregation‐induced emission characteristics (AIEgen) was developed for cancer cell imaging and photodynamic ablation. The fluorescence is immediately turned on upon click reaction with azide‐functionalized glycans on a cancer cell surface.